Sukuk Development in Morocco: Lessons from an International Benchmark - Nokairi, Wafia; Lotfi, Said; Bennani, Inas (Theoretical and Practical Research in Economic Fields, 2026)
Objective: This study aims to assess the feasibility of developing the Sukuk market in Morocco by conducting an international benchmarking analysis of mature markets such as Malaysia, Indonesia, the United Arab Emirates, Saudi Arabia, and Bahrain, as well as initiatives in the United Kingdom and France, to provide recommendations tailored to the context. Methodology: The research is based on a comprehensive review of secondary data, including reports and publications from recognized international organizations. A comparative analysis is conducted to identify key success factors and lessons applicable to the Moroccan market, given its limited experience, notably the first sovereign issuance in 2018. Conclusions: The results show that the development of Sukuk markets depends mainly on the clarity of regulatory frameworks, the presence of regular sovereign issuances, and the role of public actors. The international benchmark reveals that some of these elements can be mobilized in the Moroccan context, while other factors, particularly those related to market size and investor base, still constitute constraints to the development of the Sukuk market. Originality: This study provides a contextual analysis of the Moroccan Sukuk market, combining lessons learned from international best practices with practical recommendations for strengthening Islamic finance in Morocco. It highlights concrete strategies for regulators, financial institutions, and investors to promote market development. Limitations: The study is based on secondary data; empirical validation through market research and stakeholder interviews could further refine the recommendations. Practical implications: The findings can guide policymakers and financial actors in designing regulatory and financial innovations aimed at developing the Sukuk market. Social implications: The development of the Sukuk market can contribute to inclusive financing solutions and promote alternative investment options, thereby supporting broader economic growth in Morocco.